Stereophonic acoustic echo canceller without pre-processing - Hirano, A.; Nakayama, K.; Someda, D.; Tanaka, M. (2004 IEEE International Conference on Acoustics, Speech and Signal Processing, 2004)
This paper proposes a stereophonic acoustic echo canceller without pre-processing which can identify the correct echo-paths. By dividing the filter coefficients into two portions and updating one part at a time, the filter coefficient have a unique solution. Convergence analysis clarifies the condition for correct echo-path identification. For fast convergence and stable adaptation, a convergence detection and an adaptive step-size are also introduced. The modification amount of the filter coefficients detects the convergence and also determines the step-size. Computer simulations show 10dB smaller coefficient error than those of the conventional algorithms.